2022
DOI: 10.29244/avl.6.4.75-76
|View full text |Cite
|
Sign up to set email alerts
|

Resistansi Escherichia coli asal feses sapi di wilayah Bogor terhadap antimikrob

Abstract: Resistansi bakteri terhadap antimikrob telah menjadi permasalahan global. Pengujian resistansi antimikrob bakteri dari hewan penting dilakukan terutama dengan adanya resistansi antimikrob pada manusia yang diduga bersumber pada ternak. Tujuan penelitian ini adalah untuk menganalisis gambaran resistansi Escherichia coli (E. coli) yang diisolasi dari feses sapi terhadap berbagai antimikrob, yaitu aztreonam, basitrasin, sefpodoksim, enrofloksasin, fosfomisin, gentamisin, dan kloramfenikol. Uji resistansi antimikr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The findings revealed that all the samples exhibited susceptibility to chloramphenicol and an intermediate susceptibility to clindamycin. Previous research conducted by Rotinsulu et al (2022) [23] has also shown considerable sensitivity to chloramphenicol in Indonesia. Moreover, a study by Akinyemi (2020) [35] found that the E. coli strain CM2555, which carried the acetyltransferase (cat) gene, was sensitive to chloramphenicol.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The findings revealed that all the samples exhibited susceptibility to chloramphenicol and an intermediate susceptibility to clindamycin. Previous research conducted by Rotinsulu et al (2022) [23] has also shown considerable sensitivity to chloramphenicol in Indonesia. Moreover, a study by Akinyemi (2020) [35] found that the E. coli strain CM2555, which carried the acetyltransferase (cat) gene, was sensitive to chloramphenicol.…”
Section: Discussionmentioning
confidence: 88%
“…Bacitracin, which is known for its bactericidal properties, disrupts the function of cell membranes, hinders protein synthesis, and restricts the growth of cell walls by blocking the synthesis of peptidoglycan strands [22]. Bacitracin is ineffective against gram-negative bacteria including E. coli [23]. However, its presence in livestock growth promoters or therapy combined with neomycin and polymyxin B needs special attention [22].…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate use of antimicrobials causes antimicrobial resistance, which is now a global problem. Previous studies reported that antimicrobial-resistant bacteria were isolated from cattle in Indonesia (Klobongona et al, 2019;Tyasningsih et al, 2021;Rotinsulu et al, 2022). In order to maximise the benefits of antimicrobial stewardship, continuous monitoring of bacterial pathogens for antimicrobial resistance is essential.…”
Section: Introductionmentioning
confidence: 99%